RETRACTED: Fatigue fracture analysis of the semi-auto shotgun mechanism by using finite element analysis and experimental setup. (November 2020) - Şen, Yaşar
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been retracted at the request of the Editor-in-Chief. The authors have plagiarized part of a paper that had already appeared in [Engineering Failure Analysis, Volume 16 (2009) 2235-2244. https://doi.org/10.1016/j.engfailanal.2009.03.014 ] One of the conditions of submission of a paper for publication is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.